ANALISIS RESPON SISWA TERHADAP PENGEMBANGAN BUKU SUPLEMEN KIMIA BERBASIS KEARIFAN LOKAL SUKU ASMAT PAPUA - Henie Poerwandar Asmaningrum; Renny Ivonny Khoe Khoe; Sukirno Sukirno (Faculty of Teacher Training and Education, Musamus University, 2018)
This study aims to determine the response of students to the development of chemical supplement books based on the local wisdom of the Asmat Tribe of Papua. The method used in this research is descriptive research with the subject of the research students of class X SMA YPPK Yos Sudarso Merauke totaling 23 students and students of class XI SMA Negeri II Merauke totaling 38 students in the 2017/2018 school year. Data collection techniques using student response questionnaires consisting of statements regarding 4 (four) aspects of assessment, namely material, presentation, language, and graphics with a total of 17 statements. The results of the student response questionnaire analysis on the development of chemical supplement books based on the local wisdom of the Asmat Tribe of Papua, the average percentage of the total response was 84,36% in the feasible category. The average percentage of student responses for each aspect, namely the material aspect of 80,13%, the presentation aspect of 85,72%, the language aspect of 85,58%, and the graphic aspect of 86,02% are also categorized as feasible. Keywords: student response, supplement book, chemistry, local wisdom